Christmas books for children - Giddens, Eugene ca. 20./21. Jh (Cambridge University Press, 2019)
This Element traces the varied and magical history of Christmas publications for children. The Christmas book market has played an important role in the growth of children's literature, from well-loved classics to more ephemeral annuals and gift books. Starting with the eighteenth century and continuing to recent sales successes and picturebooks, Christmas Books for Children investigates continuities and new trends in this hugely significant part of the children's book market
Keywords: Geschichte 1700-; Children / Books and reading / History; Children's literature / Publishing / History; Christmas in literature; Children in literature; Kinderliteratur; Weihnachten -- Motiv; Weihnachten; Christmas stories; Christmas stories / History and criticism